Implications of preoperative arterial stiffness for patients treated with endovascular repair of abdominal aortic aneurysms - Carly Thaxton, MD; Masaki Kano, MD, PhD; Daniel Mendes-Pinto, MD, PhD; Túlio Pinho Navarro, MD, PhD; Toshiya Nishibe, MD, PhD; Alan Dardik, MD, PhD (JVS - Vascular Science)
Arterial stiffening is associated with adverse cardiovascular patient outcomes; stiffness may also be associated with postsurgical events and has been suggested to be a fundamental mechanism in the pathogenesis of aortic aneurysms. Although open repair of aneurysms decreases aortic stiffness, implantation of a rigid endograft is associated with increased aortic stiffness after endovascular aneurysm repair (EVAR). This review provides an overview of aortic wall physiology and the contemporary understanding of aortic stiffness and its implications for patients undergoing abdominal aortic aneurysm repair. Recent data suggests that increased central arterial stiffness, estimated preoperatively using the pulse wave velocity (PWV), may predict aneurysm sac behavior after EVAR, with elevated preoperative PWV associated with less sac shrinkage, and even sac enlargement, after EVAR. With the development of several simple noninvasive methods to measure PWV, such as brachial-ankle PWV and single cuff brachial oscillometry, there may be a role for monitoring ambulatory PWV to predict outcomes after EVAR. Additionally, because aortic stiffness is associated with adverse cardiovascular outcomes, and EVAR increases aortic stiffness, assessment of aortic stiffness before aortic interventions may help to guide therapeutic decisions as well as surveillance protocols, leading to optimized patient outcomes.